2009
DOI: 10.1111/j.1365-2435.2009.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the potential for conflicting selection on floral chemical traits by pollinators and herbivores: predictions and case study

Abstract: Summary1. There are myriad ways in which pollinators and herbivores can interact via the evolutionary and behavioural responses of their host plants. 2. Given that both herbivores and pollinators consume and are dependent upon plant-derived nutrients and secondary metabolites, and utilize plant signals, plant chemistry should be one of the major factors mediating these interactions. 3. Here we build upon a conceptual framework for understanding plant-mediated interactions of pollinators and herbivores. We focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
271
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(295 citation statements)
references
References 117 publications
10
271
4
Order By: Relevance
“…Alternatively, there may exist indirect interactions among herbivores, plants, and pollinators that may collectively favor the evolution of greater inducibility in inbreeding taxa. Herbivory can alter floral phenotypes and influence pollinators (31,43,44), and the induction of deterrent or toxic metabolites in reward tissues such as pollen and nectar could be disproportionately costly to obligately outcrossing, compared with inbreeding, taxa (45). Because of the ancestral nature of SI in this family, a hypothesis of repeated herbivore-mediated shifts in both defense strategy and mating system seems less likely, although we note that our data cannot unequivocally exclude this possibility.…”
Section: Resultscontrasting
confidence: 40%
“…Alternatively, there may exist indirect interactions among herbivores, plants, and pollinators that may collectively favor the evolution of greater inducibility in inbreeding taxa. Herbivory can alter floral phenotypes and influence pollinators (31,43,44), and the induction of deterrent or toxic metabolites in reward tissues such as pollen and nectar could be disproportionately costly to obligately outcrossing, compared with inbreeding, taxa (45). Because of the ancestral nature of SI in this family, a hypothesis of repeated herbivore-mediated shifts in both defense strategy and mating system seems less likely, although we note that our data cannot unequivocally exclude this possibility.…”
Section: Resultscontrasting
confidence: 40%
“…Herbivory may change other floral traits that influence pollinator attraction and behavior. Recent experiments have shown that floral volatile blends can change following herbivore damage (Theis et al 2009), sometimes with consequences for pollinator behavior (Kessler and Halitschke 2009). However, timing of damage may be critical (Effmert et al 2008), and we found no effect of herbivory on floral volatiles.…”
Section: Indirect Effects On Mutualistscontrasting
confidence: 35%
“…Herbivore feeding guilds have been found to differ in their effect on flower visitors (Rusman et al 2018), and dual infestation of herbivores on the leaves may potentially further modulate these effects. Leaf-feeding herbivores may thereby strongly affect plant reproductive success when they affect arrival of herbivores that feed on flowers or seed pods (McArt et al 2013) or interactions with pollinators (Kessler and Halitschke 2009, Lucas-Barbosa et al 2011. In our study, we found that the impact on seed set was not significant and dependent on the plant population.…”
Section: Discussionmentioning
confidence: 50%
“…This could be explained by different processes that are non-exclusive: 1) the physical movement of insects from leaves towards flowers as the season progressed, 2) systemic induction of phenotypic changes i.e. leaf herbivory causes phenotypic changes in the reproductive parts (McCall and Irwin 2006, Kessler and Halitschke 2009, Lucas-Barbosa et al 2011, or 3) effects of induced plant phenotypic changes cascaded via consecutive community members up to species that are associated with flowers in a spatial-temporal manner (Utsumi et al 2010). Herbivore feeding guilds have been found to differ in their effect on flower visitors (Rusman et al 2018), and dual infestation of herbivores on the leaves may potentially further modulate these effects.…”
Section: Discussionmentioning
confidence: 99%